ANALISIS KELAYAKAN USAHA PADA UMKM ARAK CAMPUR DI DESA MAS UBUD - Ni Pande Kadek Candraningsih; Wayan Ardani; Ni Ketut Murdani (Universitas Mahendradatta, 2022)
The purpose of this study is to determine the feasibility of the ArakAlcohol Business at Mas Village. This research is a qualitative-quantitativedescriptive study with the subject of the study, was Tutmang's Bar and Kitchen andthe object of the research is the feasibility of the arak business. The methods used indata collection were interview and documentation. This study used an analysis ofNon-financial aspects in the form of legal aspects, marketing aspects, technicalaspects, and management aspects. While the financial aspect used the PaybackPeriod (PP), Net Present Value (NPV), Profitability Index (PI), Internal Rate ofReturn (IRR), Average Rate of Return (ARR) method. The result from the marketing aspect, technical aspect and management aspect showed that the arak business arefeasible, because they met most of the business appraisal criteria however from thelegal aspect it was declared not feasible because they did not have any businesslicenses. Judging from the financial aspect, Tutmang's Bar and Kitchen wasdeclared feasible because it met all the criteria in the feasibility requirements of abusiness.